Differences in Portfolios across Countries: Economic Environment versus Household Characteristics - Christelis, Dimitris; Georgarakos, Dimitris; Haliassos, Michael (The Review of Economics and Statistics, 2013)
We use cross-country microdata and counterfactual methods to document international differences in ownership and holdings of stocks, private businesses, homes, and mortgages among older households in thirteen countries. We decompose these differences into two parts, related to population characteristics and economic environments. Shortly prior to the recent financial crisis, U.S. households tended to invest more in stocks and less in homes and to have larger mortgages than Europeans of similar characteristics. Differences in ownership and amounts are primarily linked to differences in economic environments that are more pronounced among European countries than among U.S. regions, suggesting considerable potential for harmonization.